Preparation and Performance Testing of Composite Adsorbents for Solar Adsorption Refrigeration - Lingbao Wang; Xianbiao Bu; Huashan Li; Weibin Ma (Adsorption Science & Technology)
In order to develop a high-performance adsorbent for solar adsorption refrigeration, a series of composite adsorbents is prepared by impregnating CaCl 2 into the pores of silica gel. Seven samples are prepared using various concentrations of CaCl 2 aqueous solutions. Sorption properties of the samples are tested with gravimetric method. The test results indicate that both the adsorption amount and adsorption rate of the composite adsorbents increase significantly compared with that of the pure silica gel. The water uptakes of silica gel and composite adsorbent are 1.96 and 8.08 kg/100 kg adsorbents, respectively, with the relative humidity of 20% and adsorption time of 20 minutes. Subsequently, a novel solar adsorption chiller is designed, in which the composite adsorbent is used as an adsorbent and water as a refrigerant. Performance testing of the adsorption chiller shows that the cooling capacity, specific cooling power and coefficient of performance are 1.03 kW, 128.3 W/kg and 0.27, respectively, when hot water temperature, cooling water temperature and circulation time are 90 °C, 35 °C and 15 minutes.